2022
DOI: 10.1007/s13204-021-02295-4
|View full text |Cite
|
Sign up to set email alerts
|

Green nanofiber mat from HLM–PVA–Pectin (Hibiscus leaves mucilage–polyvinyl alcohol–pectin) polymeric blend using electrospinning technique as a novel material in wound-healing process

Abstract: The present work is focused on fabrication of novel nanofiber (NF) mat as wound-healing scaffold using blends of novel combination of Hibiscus rosa-sinensis leaves mucilage (HLM)–Polyvinyl alcohol (PVA)–Pectin, which was never reported previously. Different ratios of the polymeric blends were electrospun by setting different parameters to achieve best possible electrospun nanofiber mat which was later crosslinked by glutaraldehyde vapor. The optimized formulation of nanofiber mat was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There is also a report on other blends for electrospinning. Sen et al [ 88 ] prepared a blend of two natural polymers (hibiscus leaves mucilage and pectin) and a synthetic polymer (polyvinyl alcohol) by electrospinning technique for the wound healing process. It was found that hibiscus leaves, mucilage, and pectin in nanofiber scaffolds have been effective for wound treatment.…”
Section: Electrospun Nanofibers In the Biomedical Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a report on other blends for electrospinning. Sen et al [ 88 ] prepared a blend of two natural polymers (hibiscus leaves mucilage and pectin) and a synthetic polymer (polyvinyl alcohol) by electrospinning technique for the wound healing process. It was found that hibiscus leaves, mucilage, and pectin in nanofiber scaffolds have been effective for wound treatment.…”
Section: Electrospun Nanofibers In the Biomedical Fieldmentioning
confidence: 99%
“…Electrospinning and film casting methods are used for poly- L -lactic acid (PLA) and chitosan blends [ 88 , 94 ]. PLA/chitosan blend acts as wound dressing material, and it can form an effective barrier against bacteria [ 95 ].…”
Section: Electrospun Nanofibers In the Biomedical Fieldmentioning
confidence: 99%
“…An interesting valorization of a plant mucilage’s properties (especially charge density here) involves electrospinning, a modern technique applied to obtain nanofibers. Nanofibrillated mats and patches are considered ideal wound healing materials, allowing a sufficient oxygen supply and facile incorporation of the API [ 37 ]. A Plantago ovata mucilage was used as a precursor for the preparation of core–shell nanofibers.…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%
“…1 It is traditionally used as a gelling and thickening agent in the food and pharmaceutical industries. Apart from its known health benefits, 2 novel applications such as preparation of food matrixes containing added nutrients, 3 prebiotics, 4 modification of viscosity of other carbohydrates, 5 food preservation and packaging, 6 emulsion stabilizer, 7 biosorption, 8 targeted drug delivery, 9 controlled drug release, 10 preparation of drugencapsulated emulsion gels 11 and nanoparticles, 12 wound healing, 13 tissue engineering, 14 bioprinting, 15 energy storage, 16 etc. have been developed using pectin-based composites.…”
Section: Introductionmentioning
confidence: 99%